TRIANGLE Knowledge Alliance - (:unkn) unknown (My University, 2026)
Appointed as the contact person for CUT-Heraclitus Research Centre to deal with the Alliance network management. The ECOTRANS Network for Sustainable Tourism has teamed up with leading European Universities-University of Algarve (Portugal), Eberswalde University (Germany), Paris 1 Panthéon-Sorbonne University (France) and MODUL University Vienna - and businesses with core ICT and tourism interests to create a collaborative online learning system for Higher Education Institutes (HEI), based on innovation and cooperation that will offer quality training on Tourism Sustainability.